2020
DOI: 10.3389/fnmol.2020.574947
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Prefrontal Neuronal Activity and Social Dominance Behavior in Postnatal Forebrain Excitatory Neuron-Specific Cyfip2 Knock-Out Mice

Abstract: The cytoplasmic fragile X mental retardation 1 (FMR1)-interacting protein 2 (CYFIP2) gene is associated with epilepsy, intellectual disability (ID), and developmental delay, suggesting its critical role in proper neuronal development and function. CYFIP2 is involved in regulating cellular actin dynamics and also interacts with RNA-binding proteins. However, the adult brain function of CYFIP2 remains unclear because investigations thus far are limited to Cyfip2 heterozygous (Cyfip2 +/−) mice owing to the perina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…The mPFC was previously regarded as the major brain region governing social dominance (Tan et al, 2018;Zhang et al, 2020;Zhou et al, 2018). In parallel, only cortical HDAC2 was able to influence agonistic outcomes, while its expression in the hippocampus did not have the same effect (Figure 4J).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The mPFC was previously regarded as the major brain region governing social dominance (Tan et al, 2018;Zhang et al, 2020;Zhou et al, 2018). In parallel, only cortical HDAC2 was able to influence agonistic outcomes, while its expression in the hippocampus did not have the same effect (Figure 4J).…”
Section: Discussionmentioning
confidence: 85%
“…Electrophysiological recordings mEPSC recordings were performed in whole-cell configuration under voltage-clamp mode at -70 mV holding potentials as described previously (Zhang et al, 2020), with minor modifications. Briefly, coronal slices of mPFC were prepared (300 mm thickness), and transferred to a storage chamber in an incubator filled with oxygenated artificial cerebrospinal fluid (ACSF), which contained 124 mM NaCl, 2.5 mM KCl, 1.23 mM NaH 2 PO 4 , 1.5 mM MgCl 2 , 2.5 mM CaCl 2 , 26 mM NaHCO 3 and 10-dextrose.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence suggest that CYFIP1 and CYFIP2 proteins have both shared and distinct functions in neurons. For example, we recently reported that in layer 2/3 neurons of the medial prefrontal cortex of Cyfip2 conditional knock‐out (cKO) mice, CYFIP1 proteins were upregulated as a compensation, to maintain normal F‐actin levels (Zhang et al, 2020). However, in the same neurons of cKO mice, hyperexcitability was still observed, suggesting that CYFIP1 cannot compensate for CYFIP2 functional regulation of neuronal excitability (Lee, Zhang, Kang, et al, 2020; Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Whole lysates of the mouse tissue were prepared as previously described (Zhang et al, 2018; Zhang et al, 2020). Briefly, frozen mouse brain tissue was homogenized in RIPA buffer (50 mM Tris–HCl pH 8.0, 150 mM NaCl, 0.1% SDS, 1% Triton X‐100, 0.5% sodium deoxycholate) with freshly added protease and phosphatase inhibitors (Sigma‐Aldrich, #05892970001 and #04906837001, respectively).…”
Section: Methodsmentioning
confidence: 99%